CHINA’S NATIONAL INTEREST AS THE MAIN CONDUCTOR OF UIGHUR ISSUES - Antar Zidane (UNIVERSITAS SEBELAS MARET (UNS), 2020)
This scientific paper examines the main factors causing the Uighur issue. The problems contained in the Uighur issue are complex problems that make the existence of a scientific work examining this issue urgent. Because, this problem has become one of the popular issues, especially in the study of International Relations in the contemporary period. So that encourages the writer to study this problem and provide a spectrum of Uighur issues through this scientific paper. This scientific paper is made by the writer using qualitative methods that refer to credible sources as a reference related to the main factors that are conductors of Uighur issues. In this scientific paper, the author has found that China's national interest in the form of territories in places used as homes by ethnic Uighurs are the main variable on the conductors of Uighur issues.Keywords: China; Issue; National Interest; Uighur. AbstrakKarya tulis ilmiah ini mengkaji tentang faktor-faktor utama yang menyebabkan isu Uighur. Masalah yang terkandung dalam isu Uighur merupakan permasalahan kompleks yang menjadikan eksistensi karya tulis ilmiah yang mengkaji isu ini berurgensi tinggi. Karena isu ini telah menjadi salah satu masalah yang populer, terutama dalam studi Hubungan Internasional di masa kontemporer. Sehingga hal ini mendorong penulis untuk mengkaji masalah ini dan memberikan spektrum isu Uighur melalui karya tulis ilmiah ini. Karya tulis ini dibuat oleh penulis menggunakan metode kualitatif yang merujuk pada sumber-sumber yang bersifat credible sebagai referensi terkait dengan faktor utama yang menjadi konduktor isu Uighur. Dalam karya tulis ilmiah ini, penulis telah menemukan bahwa kepentingan nasional China dalam bentuk teritori di tempat-tempat yang digunakan sebagai tempat tinggal oleh etnis Uighur adalah variabel utama pada konduktor masalah Uighur.Kata kunci: China; Issue; National Interest; Uighur.